Analisis Welding Joint Performance Material ASTM SA 178 D Pada Waterwall Tube Boiler PLTU Paion Unit 1-400 - Arief Suardi Nc; Paltiraja Paltiraja (Sekolah Tinggi Teknik - PLN, 2013)
One of the important components in the boiler waterwall tube. The main function of waterwall tube is to convert water into steam. Conducted research focused on the performance of welded joints waterwall tube boilers, where the testing is done Vikers micro test, SEM and EDAX test and Mapping, and the chemical composition of the test. Because the welding process was very important here, whether appropriate or thoroughness standards that affect the heat treatment that occurred in the boiler tube material. In this paper waterwall tube material used is a type of medium carbon steel material (Electric resistance welded carbon steel) as defined in ASTM SA178D. In the waterwall tube welded joints can also be compared in terms of both its Performance microstructure and hardness and also the spread of elements - elements contained within these materials.